Implementation of an Irrigation System to Estimate Water in Hydroponic Crops through Evapotranspiration - Jorge Hernandez; Karen Daza (ParadigmPlus, 2021)
Hydroponic crops is a special type of crop because it tries to reduce space and water use for certain plants. Normally, the estimation of the water of the crops in underdeveloped countries is made in a manual way generating waste of water. In the water estimation, ideal factors can be considered in which the crops carry out their biological process with a high yield. The hydric estimation can be measured as a function of the soil, the ambient temperature, the diameters of the roots, and the interspace between the plants. We consider carrying out the water estimation checking each plant to reach the correct progress of plants in the crop. We show an approach to integrating hardware and software components. The prototype is capable of calculating the evapotranspiration of crops and making a water estimation according to the several factors in each plant and the measured data from electronic sensors in order to reduce water in each irrigation. Additionally, the system allows the farmers to schedule the irrigation.